THE CONSTRUCTIONIST HISTORIOGRAPHY OF GREEK EROTICS (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
The article analyzes the postmodern and foucaultian view of the theoretical field and methodologies of some works of the Constructionist Historiography that engaged with the study of Greek erotic since the 1980s, trying to reveal their ties to the New Cultural History.